SA01 – A Proposed Zircon Reference Material for Microbeam U‐Pb Age and Hf‐O Isotopic Determination. Issue 1 (26th December 2019) - Huang, Chao; Wang, Hao; Yang, Jin‐Hui; Ramezani, Jahandar; Yang, Chuan; Zhang, Shao‐Bing; Yang, Yue‐Heng; Xia, Xiao‐Ping; Feng, Lian‐Jun; Lin, Jie; Wang, Tian‐Tian; Ma, Qian; et al.
Abstract : A new natural zircon reference material SA01 is introduced for U‐Pb geochronology as well as O and Hf isotope geochemistry by microbeam techniques. The zircon megacryst is homogeneous with respect to U‐Pb, O and Hf isotopes based on a large number of measurements by laser ablation‐inductively coupled plasma‐mass spectrometry (LA‐ICP‐MS) and secondary ion mass spectrometry (SIMS). Chemical abrasion isotope dilution thermal ionisation mass spectrometry (CA‐ID‐TIMS) U‐Pb isotopic analyses produced a mean 206 Pb/ 238 U age of 535.08 ± 0.32 Ma (2 s, n = 10). Results of SIMS and LA‐ICP‐MS analyses on individual shards are consistent with the TIMS ages within uncertainty. The δ 18 O value determined by laser fluorination is 6.16 ± 0.26‰ (2 s, n = 14), and the mean 176 Hf/ 177 Hf ratio determined by solution MC‐ICP‐MS is 0.282293 ± 0.000007 (2 s, n = 30), which are in good agreement with the statistical mean of microbeam analyses. The megacryst is characterised by significant localised variations in Th/U ratio (0.328–4.269) and Li isotopic ratio (−5.5 to +7.9‰); the latter makes it unsuitable as a lithium isotope reference material. Abstract : Keypoints: The homogeneity of the SA01 zircon megacryst was assessed by microbeam techniques for U‐Pb geochronology, and Li, O and Hf isotope geochemistry. SA01 is homogeneous in terms of U‐Pb, O and Hf isotopes. SA01 is unsuitable as a lithium isotope reference material.